1994
DOI: 10.1136/jnnp.57.8.921
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin and lamotrigine in refractory epilepsy.

Abstract: Epilepsy arises from an imbalance of inhibitory and excitatory influences in the brain. Vigabatrin (VIG) decreases the breakdown of the inhibitory neurotransmitter y-aminobutyric acid, whereas lamotrigine (LTG) reduces presynaptic excitatory amino acid release. 22 patients with refractory epilepsy, treated with an anticonvulsant regimen containing VIG, entered a balanced, double blind, placebo controlled, crossover trial of additional LTG. Treatment periods of 12 weeks (25 mg, 50 mg, 100 mg LTG twice daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Twelve crossover trials 40,55,82,89,91,134,136,[158][159][160][161][162] and two parallel trials 137,142 compared adjunctive LTG with placebo in patients with refractory epilepsy. One trial included only patients with partial seizures 162 and another only patients with generalised seizures.…”
Section: -155mentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve crossover trials 40,55,82,89,91,134,136,[158][159][160][161][162] and two parallel trials 137,142 compared adjunctive LTG with placebo in patients with refractory epilepsy. One trial included only patients with partial seizures 162 and another only patients with generalised seizures.…”
Section: -155mentioning
confidence: 99%
“…One trial included only patients with partial seizures 162 and another only patients with generalised seizures. 134 The remainder of the trials included patients with either partial or generalised seizures.…”
Section: -155mentioning
confidence: 99%
See 1 more Smart Citation
“…Although no study has compared the efficacy of these medications separately, we found that in both groups, when treated with CBZ or LMT alone, patients experienced adverse effects and/or insufficient pain control. A number of authors have reported the use of combination antiepileptic drugs with similar or different pharmacodynamic profiles for the treatment of nonrespondent seizures [9, 10, 11, 12]. We evaluated whether combination therapy of medications with different mechanisms of action could produce clinical benefit while reducing adverse effects, since many MS patients are sensitive to drugs with CNS effects, even in small doses.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized placebo-controlled trials have clearly shown that oxcarbazepine [53,[81][82][83][84][85], Lamotrigine-vigabatrin Partial seizures Anecdotical [162] Tiagabine-vigabatrin Partial seizures Anecdotical [163] Lamotrigine-gabapentin Partial seizures Anecdotical [164] Lamotrigine-topiramate Partial seizures Anecdotical [165] tiagabine [8,9,86,87], gabapentin [30,88] and vigabatrin [7,[89][90][91][92] are effective against partial seizures (with or without secondary generalization) and, possibly, also against primarily generalized tonic-clonic seizures. In addition, vigabatrin shows remarkable value in the treatment of infantile spasms, especially those associated with tuberous sclerosis [93][94][95][96].…”
Section: Efficacy Spectrum In Different Seizure Typesmentioning
confidence: 99%